Impact of the decarbonisation of the energy system on employment in Europe - Behrens, Arno; Coulie, Caroline; Genoese, Fabio; Alessi, Monica; Wieczorkiewicz, Julian; Egenhofer, Christian (Brussels, 2014)
"This paper presents a methodology for calculating the potential impact of the new socio-ecological transition away from fossil fuels on employment in EU energy supply. The methodology is based on “employment factors” (i.e. labour intensities) of different energy technologies. These employment factors are applied to changing energy mixes as projected by the decarbonisation scenarios of the European Commission’s Energy Roadmap 2050. In particular, we analyse quantitative (number of jobs) and qualitative (qualification levels) impacts on employment in extraction and processing of primary (fossil) fuels and in the power sector for the years 2020, 2030 and 2050. The results show that the energy sector will provide not only more jobs as the new socio-ecological transition unfolds, but also jobs requiring higher-level qualifications when compared with the current energy sector."